2023
DOI: 10.1186/s13058-023-01633-4
|View full text |Cite|
|
Sign up to set email alerts
|

National and subnational burden of female and male breast cancer and risk factors in Iran from 1990 to 2019: results from the Global Burden of Disease study 2019

Abstract: Background Breast cancer (BC) is one of the most burdensome cancers worldwide. Despite advancements in diagnostic and treatment modalities, developing countries are still dealing with increasing burdens and existing disparities. This study provides estimates of BC burden and associated risk factors in Iran at the national and subnational levels over 30 years (1990–2019). Methods Data on BC burden for Iran were retrieved from the Global Burden of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…There are approximately 464,000 new cases of breast cancer (29% of all new cancers) in Europe and 131,000 breast cancer specific deaths, which accounts for 17% of all cancer deaths [ 3 ]. Earlier studies in Iran have estimated that the prevalence of breast cancer was 120 per 100,000 among adult women [ 4 ]. It accounts for more than 20% of all cancers in Iran [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 464,000 new cases of breast cancer (29% of all new cancers) in Europe and 131,000 breast cancer specific deaths, which accounts for 17% of all cancer deaths [ 3 ]. Earlier studies in Iran have estimated that the prevalence of breast cancer was 120 per 100,000 among adult women [ 4 ]. It accounts for more than 20% of all cancers in Iran [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 In Iran, the age‐standardized incidence rate of breast cancer escalated from 18.8 per 100 000 in 1990 to 34.0 per 100 000 in 2019 among females and from 0.2 to 0.3 per 100 000 among males. 3 Advancements in oncology, surgery, and treatments such as radiotherapy, chemotherapy, and hormone therapy have significantly improved the survival rate of breast cancer patients, with over 90% surviving for 5 years. 4 , 5 Nonetheless, these treatments, especially chemotherapy, have adverse effects on various aspects of the well‐being of breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“… 2 how long does CRCI last after completing chemotherapy? and 3 what is the long‐term effect of using chemotherapy on cognitive functions?…”
Section: Introductionmentioning
confidence: 99%
“…Another study in 2016 reported an ASIR of 40.72 per 100,000 women (6). The study of the national and subnational burden of breast cancer in women and men in Iran from 1990 to 2019 showed that the ASIR among women in 2019 was 34.0 (30.7 -37.9)/100,000 and from 0.2/100,000 (0.2 -0.3) to 0.3/100,000 (0.3 -0.4) among men (7).…”
Section: Introductionmentioning
confidence: 99%